Plasma concentration estimates of thirty trace elements in Xuanwei and Fuyuan, two high lung cancer incidence areas in China - Zhang, Linlin; Ge, Yiwen; Lv, Jungang (Trace elements and electrolytes, 2024)
In Xuanwei and Fuyuan, located in the southwest of Yunnan province, China, an exceptionally high incidence of lung cancer has been observed. Although numerous factors have been investigated, the association between lung cancer and trace elements lacks sufficient exploration. In this study, 190 plasma samples from local lung cancer patients and a control group were collected. Microwave digestion method was used for sample pretreatment. ICP-MS was used to quantify concentrations of 30 trace elements. This analysis encompassed the distribution levels of different elements in plasma, comparison between the patient and control group, and the identification of key elements and their correlations with lung cancer through multiple regression equation and correlation tests. The plasma trace element concentrations were measured in 96 lung cancer patients and 94 control subjects. The concentration levels provide valuable benchmarks for relevant studies. Statistical analysis was conducted using SAS statistical software for normal distribution, followed by group comparisons via t-tests. The results showed disparities in 13 elements between the lung cancer group and the control group: 7 elements were significantly higher in the lung cancer group, while 6 elements were markedly lower. In the multi-factor analysis, Cu emerged as a potential risk factor for lung cancer, whereas Zn and Se appeared to be protective factors. Multivariate correlation analysis was used to analyze Cu, Zn, and Se. The upper limit of the normal value was set at 1.41, which was the upper limit of the 95% confidence interval of the Cu/Zn ratio in the control group. Notably, 80 lung cancer patients had a Cu/Zn ratio exceeding this threshold, representing 84.2% (80/95) of the cases studied.